2013
DOI: 10.1002/jsfa.6178
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the processing of Perna perna mussels: the influence of water quality involved in the cooling operations in the physico‐chemical and microbiological characteristics of the product

Abstract: The study shows that microbiological cross-contamination occurred during the processing of mussels. Rigorous control is necessary from the production area of mussels to retailers. Good manufacturing practices must be implemented in the industry and cross-contamination avoided, mainly by Vibrio spp. after heat treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 29 publications
(49 reference statements)
0
15
0
2
Order By: Relevance
“…This indicates that the procedures adopted are able to avoid recontamination in the mussel as reported by Lima et al . (), who found mussel recontamination by Vibrio spp. after cooling operations and during product storage.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This indicates that the procedures adopted are able to avoid recontamination in the mussel as reported by Lima et al . (), who found mussel recontamination by Vibrio spp. after cooling operations and during product storage.…”
Section: Resultsmentioning
confidence: 99%
“…The results are also similar to those obtained by Lima et al . (), who evaluated the pH of precooked processed mussels and found that the changes in pH during storage were associated with failures in processing, resulting in product deterioration. Erkan () studied cooked mussels of the species Mytilus galloprovincialis during storage at 4C and obtained no significant reduction in pH over 6 days of storage (5.96–5.89).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A textura normalmente é o parâmetro mais afetado pelos tratamentos com alta pressão. Conforme Murchie et al, (2005), os alimentos apresentam características mais rígidas quando submetidos a esse processo, entretanto isso não aconteceu com os mexilhões tratados neste estudo.…”
Section: Avaliação Físico-química Dos Mexilhões No Armazenamentounclassified
“…Moluscos bivalves, como os mexilhões, são animais filtrantes das águas que os circundam, e por isso retém micro-organismos e outras partículas que os tornam extremamente perecíveis (Lima et al, 2013). Existem várias técnicas capazes de garantir a segurança do produto, porém com prejuízo na característica sensorial.…”
Section: Introductionunclassified